Penerapan Maqhasid Syariah Pada Ekonomi Hijau Bidang Pertanian dan Lingkunagna Hidup di Kabupaten Belitung Timur - Amrizal; Muhammad Amin Pohan; Hardi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of the research is to analyze the implementation, explore the factors and benefits of implementing maqasid syari'ah for oil palm, pepper, coffee and soybean farmers in Dendang District, East Belitung Regency. The research method uses descriptive qualitative with case studies, where collective data uses in-depth interviews, observations and document data while data analysis uses qualitative data analysis by reducing, mapping and reducing data obtained from the field. The research results prove that the understanding and implementation of Maqasid Syariah is, first, environmental maintenance (Hifz al-Bi'ah) where farmers in Dendang District have not adopted environmentally friendly agricultural practices, such as the use of organic fertilizer and efficient water management. Second, Social Justice (Hifz al-'Adl) Where the distribution of agricultural products is carried out fairly, ensuring welfare for all members of the community, including those who are less fortunate. Third, Economic Welfare (Hifz al-Mal) where farmers' income has not increased optimally because they have not implemented sustainable agricultural technology and better market access. Fourth, Agricultural Sustainability Where sustainable agricultural practices have not reduced negative impacts on the environment, such as land degradation and water pollution. Fifth, crop diversification and the use of local varieties that are resistant to climate change help improve food security and the local economy. Community Involvement Where active community participation has not been maximized in environmental and sustainable agricultural programs.